The effect of silicon dioxide and zinc borate on the flame retardancy, thermal and mechanical properties of jute/epoxy hybrid composite - Canitez, Hurrem; Yilmaz, Ayten Nur Yuksel; Bedeloglu, Ayse celik (Taylor & Francis Inc, 2023)
With the increase in environmental pollution, studies on the use of sustainable resources are increasing day by day. For this purpose, the use of natural fiber-reinforced polymer composites is encouraged in many areas such as automotive, transportation, construction, and home textiles. However, they are flammable and therefore seriously threaten the safety of people and property. Various flame retardant additives have been used to improve the flame retardancy properties of these composites. In this study, silicon dioxide (SD) and zinc borate (ZB) microparticles in different weight percentages (3, 5, 7, and 10%) were reinforced to give flame retardant properties to jute-epoxy composites. In addition, composites containing both SD and ZB microparticles were produced and they were labeled as HB. Then, thermal conductivity, flammability, water absorption, and mechanical properties of these composites were investigated. The burning rate of the composites decreased as the amount of microparticle increased. 5ZB5SD, including %5 SD and %5 SD microparticles, showed 36.60% less burning rate than the neat jute-epoxy composite. 5ZB showed 10.84% higher tensile strength than the neat jute-epoxy. The impact strength of the specimens increased with the increase in the filling ratio, and 5ZB5SD showed approximately 2.50 times the impact strength of the jute-epoxy composite.
Keywords: Natural fiber; zinc borate; silicon dioxide; flame retardant; mechanical properties; hybrid composites